Do you make these mistakes in English? : the story of Sherwin Cody's famous language school - Battistella, Edwin L. (Oxford : Oxford University Press, 2008)
Linguist Edwin Battistella tells the story of Sherwin Cody and his famous English course, situating both the man and the course in early-20th century cultural history. The author shows how Cody became a grammatical entrepreneur and mass-marketer whose ads asked 'Is Good English Worth 25 Cents to You?'.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Cody, Sherwin, -- 1868-1959.; English teachers -- United States -- Biography; Businesspeople -- United States -- Biography; Language and culture -- United States -- History -- 20th century; Correspondence schools and courses -- History -- 20th century; English language -- Rhetoric -- Study and teaching